The impact of pesticide and fertiliser use on agricultural productivity in the context of the 'farm to fork' strategy in romania and the european union - Cosmin Dobrin; Elena Oana Croitoru; Ruxandra Dinulescu; Irinel Marin (Amfiteatru Economic Journal, 2022)
One of the main pillars of the European Green Pact is the "Farm to Fork" strategy. Launched in May 2020, this strategy aims to build sustainable agri-food production and distribution processes. The aim of this research is to estimate the impact of inorganic pesticide and fertiliser use on agricultural productivity and the economy at the national and European level in the context of the implementation of the "Farm to Fork" strategy. The current study outlines two models of analysis that will estimate the correlation between a possible 50% decrease in pesticide use and a 20% decrease in fertiliser use, and the level of agricultural productivity in European countries and, implicitly, Romania. The originality of the paper lies in the research method used, based on computable general equilibrium modelling, whose results were adjusted with a coefficient obtained by statistical analysis of agricultural productivity from 1991-2019. The results obtained show that the implementation of the strategy regarding the decrease in pesticides and fertilisers will not negatively influence the agricultural productivity of Romania. In addition, the amount of pesticides and fertilisers used in Romania is lower than the European average.
Keywords: D24; Q56; Q57; 330; "Farm to Fork"; agricultural productivity; fertilisers; Pesticides